Miguel Gutiérrez reader of Escalas melografiadas by César Vallejo - Jurado Párraga, Raúl (2023)
This article focuses on the critical perception of César Vallejo Mendoza’s narrative from the aesthetics of the reception of a narrator such as Miguel Gutiérrez Correa, who adoptes a didactic and critical approach to César Vallejo’s total prose, a hermeneutic entrance to Vallejo’s narrative diegesis. It also seeks to refresh the evaluation of Vallejo’s narrative outside the studies of Eduardo Neale-Silva and Antonio González Montes; and contrast the value judgements made by the author of Violencia del tiempo as a creator on the narrative work of César Vallejo in his experimental proposal of Escalas.